The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/mcp.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in narcolepsy

Abstract: Purpose Summarize the recent findings in narcolepsy focusing on the environmental and genetic risk factors in disease development. Recent findings Both genetic and epidemiological evidence point towards an autoimmune mechanism in the destruction of orexin/hypocretin neurons. Recent studies suggest both humoral and cellular immune responses in the disease development. Summary Narcolepsy is a severe sleep disorder, where neurons producing orexin/hypocretin in the hypothalamus are destroyed. The core symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 74 publications
0
30
0
4
Order By: Relevance
“…Moreover, the lateral hypothalamus hosts neurons producing orexin, a neuropeptide of fundamental importance for arousal and vigilance. In narcolepsy, a disease with dramatically reduced vigilance, autoimmunological reactions against orexin-producing neurons strongly decrease orexin levels 65. This led to the hypothesis that less pronounced reductions of orexin might produce fatigue in MS. For example, hypothalamic lesions in MS could lead to partial depletion of orexin; alternatively, immunological processes could affect the synthesis and/or postsynaptic efficacy of orexin.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lateral hypothalamus hosts neurons producing orexin, a neuropeptide of fundamental importance for arousal and vigilance. In narcolepsy, a disease with dramatically reduced vigilance, autoimmunological reactions against orexin-producing neurons strongly decrease orexin levels 65. This led to the hypothesis that less pronounced reductions of orexin might produce fatigue in MS. For example, hypothalamic lesions in MS could lead to partial depletion of orexin; alternatively, immunological processes could affect the synthesis and/or postsynaptic efficacy of orexin.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mimicry and the consequent potential cross-reactivity following infections have been repeatedly described in humans. [1][2][3][4][5][6][7][8][9][10][11][12] Such cross-reactivity is not evident in experimental infections of primates. 13 Actually, following preclinical studies performed in primates [14][15][16][17][18] as recommended by the Food and Drug Administration, 19 the reports declare that primate active immunization by pathogen vaccine administration is well tolerated and exempt of relevant events.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies have revealed a strong association of narcolepsy with the T-cell receptor alpha locus ( Hallmayer et al, 2009 ) and especially with Major Histocompatibility Complex (MHC) class II DQB1*06:02 alleles ( Bonvalet et al, 2017 ; Tafti et al, 2014 ). DQB1*06:02 is present in approximately 30% of Finnish and Swedish populations ( Bomfim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%